RESPON PENGELOLA HUTAN KOTA TARAKAN TERHADAP KELESTARIAN LINGKUNGAN - Adi Sutrisno; Mohammad Wahyu Agang (Jurnal Analisis Kebijakan Kehutanan, 2020)
Community activities in the city forest area have caused degradation and damage, therefore it requires a responsefrom the parties, especially the community in the area. The research aims to describe the supporting policies, the distribution of land area and cover, perceptions, participation, responses, and formulate policy implications. The methods used include qualitative content analysis, remote sensing land cover and geographic information systems and qualitative descriptive analysis using the PSR approach. The results of the research are: supporting policies including Government Regulations, Ministerial Regulations, Ministerial Decrees, Tarakan Mayor Regulations, and Tarakan Mayor Decrees the area has not been distributed proportionally with the dominance in the East Tarakan District, community perception is low which results in activities that are not in accordance with the designation of the land, giving birth to land tenure conditions and the user community does not participate in management. Residents are involved in sustainability and the policy implications of this research are the revised RTRW for the City of Tarakan and model of government and community partnership in management which are formulated and stipulated in the PERDA